Chromosomal aberrations in lymphocytes predict human cancer independently of exposure to carcinogens - BONASSI, S; HAGMAR, L; KNUDSEN, L. E; NORPPA, H; STROMBERG, U; MONTAGUD, A. H; TINNERBERG, H; FORNI, A; HEIKKILÄ, P; WANDERS, S; WILHARDT, P; HANSTEEN, I.-L (Cancer research (Chicago, Ill.), 2000)
An increased risk of cancer in healthy individuals with high levels of chromosomal aberrations (CAs) in peripheral blood lymphocytes has been described in recent epidemiological studies. This association did not appear to be modified by sex, age, country, or time since CA test, whereas the role played by exposure to carcinogens is still uncertain because of the requisite information concerning occupation and lifestyle was lacking. We evaluated in the present study whether CAs predicted cancer because they were the result of past exposure to carcinogens or because they were an intermediate end point in the pathway leading to disease. A nested case-control study was performed on 93 incident cancer cases and 62 deceased cancer cases coming from two prospective cohort studies performed in Nordic countries (Denmark, Finland, Norway, and Sweden) and Italy. For each case, four controls matched by country, sex, year of birth, and year of CA test were randomly selected. Occupational exposure and smoking habit were assessed by a collaborative group of occupational hygienists. Logistic regression models indicated a statistically significant increase in risk for subjects with a high level of CAs compared to those with a low level in the Nordic cohort (odds ratio, 2.35; 95% confidence interval, 1.31-4.23) and in the Italian cohort (odds ratio, 2.66; 95% confidence interval, 1.26-5.62). These estimates were not affected by the inclusion of occupational exposure level and smoking habit in the regression model. The risk for high versus low levels of CAs was similar in subjects heavily exposed to carcinogens and in those who had never, to their knowledge, been exposed to any major carcinogenic agent during their lifetime, supporting the idea that chromosome damage itself is involved in the pathway to cancer. The results have important ramifications for the understanding of the role played by sporadic chromosome damage for the origin of neoplasia-associated CAs.